2009
DOI: 10.1088/0004-637x/695/2/l163
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF A TERTIARY BROWN DWARF COMPANION IN THE sdB-TYPE ECLIPSING BINARY HS 0705+6700

Abstract: HS 0705+6700 is a short-period (P=2.3 hours), close binary containing a hot sdB-type primary and a fully convective secondary. We have monitored this eclipsing binary for more than 2 years and as a result, 32 times of light minimum were obtained. Based on our new eclipse times together with these compiled from the literature, it is discovered that the O-C curve of HS 0705+6700 shows a cyclic variation with a period of 7.15 years and a semiamplitude of 92.4 s. The periodic change was analyzed for the light-trav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 17 publications
3
63
0
Order By: Relevance
“…Qian et al (2009b) (Drechsel et al 2001;Niarchos et al 2003;Németh et al 2005;Kruspe et al 2007). They detected cyclic variations that were attributed to the light-travel time effect produced by the presence of a third object.…”
Section: Appendix A: Notes On Individual Systemsmentioning
confidence: 99%
“…Qian et al (2009b) (Drechsel et al 2001;Niarchos et al 2003;Németh et al 2005;Kruspe et al 2007). They detected cyclic variations that were attributed to the light-travel time effect produced by the presence of a third object.…”
Section: Appendix A: Notes On Individual Systemsmentioning
confidence: 99%
“…The source was subsequently monitored by Qian et al (2009Qian et al ( , 2010a, and references therein). For NSVS1425, on the other hand, there is a dearth of data between 1999 and 2007, when Wils et al (2007) noted its eclipsing nature.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…A large body of mid-eclipse times of HS0705 has been collected by Qian et al (2009Qian et al ( , 2010a and interpreted in terms of a third body with a mass of about 30 M Jup , orbiting the binary with a period of 7.15 yr. Çamurdan et al (2012) added a few timings and found a similar period. We obtained 18 more primary and three secondary eclipses of HS0705, significantly extending the coverage.…”
Section: Hs0705+6700mentioning
confidence: 99%
See 2 more Smart Citations